Use of a flow diverter with antegrade-retrograde coil embolization for an unruptured persistent primitive trigeminal artery aneurysm - Takumi Yamada (Elsevier, 2022)
Persistent primitive trigeminal artery (PPTA) is the most common primitive carotid-basilar anastomosis, and it is associated with cavernous aneurysms. Because aneurysms are supplied blood by both the internal carotid artery (ICA) and PPTA, the PPTA should be occluded for successful flow diverter treatment. Here, we report a successful case of endovascular treatment for a PPTA aneurysm using flow diverter and antegrade-retrograde coil embolization. Our case findings demonstrated that the occlusion of PPTA should be performed for a greater chance of successful flow diversion.